Desenvolvimento de hidrogéis antimicrobianos de gelatina contendo ácidos orgânicos para aplicações alimentícias - Moreira, Thaysa Fernandes Moya (2018)
Intense meat demand brings food safety concerns due to susceptibility to contamination that can lead to foodborne illness. Among the alarming factors are the nonconformities in the hygiene of equipment related to the sanitizer's inadequate action. With that, together with the need to develop green technologies and reduce water consumption, new sanitizers are on the rise. One of the alternatives is the use of organic acids, such as lactic acid and acetic acid, which have antimicrobial activity and, because they are considered safe for use in foods, do not need to be removed after application, which is not the case with sanitizers which need rinsing. The incorporation of these compounds into hydrogels, which are cross-linked polymeric structures, can be effective because of their ease production and low cost. With this, the objective of this work is to develop gelatin hydrogels containing organic acids as sanitizers for application in the internal cleaning of meat grinders. Initially, analyses of minimum inhibitory concentration and minimum bactericidal concentration of the lactic and acetic acids were carried out according to the broth microdilution method, synergism analysis in the combination of the acids through the fractional inhibitory concentration index (FIC) and time-kill for inhibition of Salmonella Typhimurium, Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli. From the evaluation of these results, enzymatically (Transglutaminase) crosslinked gelatin hydrogel formulations were produced: without addition of organic acids as control (C), containing 1xMIC lactic acid and 6xMIC (GRL1 and GRL6), containing 1xMIC acetic acid and 6xMIC (GRA1 and GRA6), containing combinations of lactic and acetic acids 1xsynergism and 6x synergism test (GRLA1 and GRLA6). The effect of the organic acids incorporation on the hydrogels was evaluated with respect to Infrared Spectroscopy by Fourier Transform (chemical interaction between hydrogels and acids), Scanning Electron Microscopy (microstructure), mechanical properties (texturometer), porosity, equilibrium swelling in Water, swelling kinetics and mathematical modeling of water absorption (Higuchi, Kosmeyers-Peppas, Peppas-Sahlin models). In addition, the antimicrobial effect of the hydrogels was analyzed in vitro by time-kill assay at times of 1, 3, 6, 12 and 24 hours. In the results it was possible to verify that lactic acid caused structural modifications responsible for the increase of porosity, cell wall compaction and the decrease of mechanical resistance, resulting in high antibacterial efficacy for all microorganisms. Meat samples were processed before and after the application of hydrogels previously hydrated in meat grinders to evaluate the quality of meat processed after sanitization with the hydrogels by pH and microbiological analysis. It was possible to verify that the meat quality after the sanitization simulation with the hydrogels remained the same. Thus, gelatin hydrogels can be a viable alternative to the use of sanitizers diluted in water, guaranteeing the proven antimicrobial efficacy in the studies.